Inventarios floristicos en bosques secundarios de la zona de Pucallpa con fines de produccion forestal - Coronado, C.; Lombardi, I.; Sabogal, C. (2002)
Twenty nine places of secondary forest aged between 5 and 25 years were evaluated in 20 agricultural units from 8 native communities in three sectors of Pucallpa (Semuya, Requena and Neshuya) in the Peruvian Amazonian. In 5,9 ha of secondary forest a total of 219 species were found, belonging to 36 botanical families, which include trees and palms, in all the categories of vegetation. Among the species classified by ages shrubs, and use groups about more representative for abundance were those corresponding to provide sawed splints, plump wood for rural constructions and the feeding group. Inside these groups, in each sector different species highlight, which it is a fact that in Nueva Requena the productive potential of secondary forests is determined by the species used by their population for self-consumption. Also, Semuya and Neshuya show this potential and it is considered that contribution of the species that, although marketed sporadically and in a small scale, they can report revenues to the farmer.